Implementing a Buddy Reading Program to Improve Reading in Young Children - Dodor, Bernice; Johnson, Clara Murphy; Desai, Priti (Universitas Negeri Semarang, 2020)
This action research evaluated effectiveness of peer assisted strategy, a buddy reading program between 21 pairs of kindergarten and first grade students in a rural school in the United States. Kindergarten students who were below reading grade level were paired with firstgrade students who were at proficient reading grade level and vice versa. The study examined how reading storybooks together for 20 minutes a day, three times a week for four weeks, impacted student attitudes toward reading, text reading comprehension (TRC), and dynamic indicators of basic early literacy skills (DIBELS). Findings showed that students enjoyed buddy reading as reflected in the pre-and posttest surveys of reading attidues. Results also suggest the buddy reading intervention had a positive effect on the end of the year mClass Reading 3D text comprehension. Implications of using this cost-effective peer engagement strategy for teaching and research are provided.